2017
DOI: 10.1111/ajo.12730
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome: Prevalence and impact on the wellbeing of Australian women aged 16–29 years

Abstract: Background: Polycystic ovarian syndrome (PCOS) is the most common condition among reproductive-aged women. However, its exact prevalence is unknown. Aims:To determine the prevalence of PCOS in Australian women aged 16-29 years using the National Institutes of Health (NIH) criteria compared to self-reported PCOS, to compare co-morbidities between the groups and to determine the most distressing aspect of a diagnosis of PCOS for these young women. Results:The prevalence of PCOS, according to the NIH criteria, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…PCOS is associated with difficulties conceiving (Melo et al , 2015; McDonnell and Hart, 2017) and, consistent with another recent Australian study (Varanasi et al , 2018), one of the main concerns of women in this study was whether or not they could become pregnant. Similar to the findings of other studies (Snyder, 2006; Avery and Braunack-Mayer, 2007; Crete and Adamshick, 2011; Satveit, 2017), women with PCOS in this study found it difficult to access information about their condition and its reproductive implications.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PCOS is associated with difficulties conceiving (Melo et al , 2015; McDonnell and Hart, 2017) and, consistent with another recent Australian study (Varanasi et al , 2018), one of the main concerns of women in this study was whether or not they could become pregnant. Similar to the findings of other studies (Snyder, 2006; Avery and Braunack-Mayer, 2007; Crete and Adamshick, 2011; Satveit, 2017), women with PCOS in this study found it difficult to access information about their condition and its reproductive implications.…”
Section: Discussionsupporting
confidence: 89%
“…Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and affects ~6–21% of women (Azziz et al , 2004; March et al , 2010; Varanasi et al , 2018). Information about PCOS usually includes that the condition is associated with fertility difficulties (Family Planning NSW, 2012; Healthdirect, 2016; Better Health Channel, 2017; Melbourne IVF, 2018; Jean Hailes for Women’s Health on behalf of the PCOS Australian Alliance, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis in 2017 reviewed the prevalence of PCOS across different ethnic groups and concluded that women from Middle Eastern countries and black women are more likely to develop PCOS as compared with Asian women . In Iran, China, and the United States, a prevalence of 3%, 2.2%, and 4.7%, respectively, has been reported; in Brazil, Beijing, Sri Lanka, Palestine, Greece, the United Kingdom, and Spain, the prevalence is reported to range from 5% to 10%, whereas Denmark, Turkey, and Australia have reported higher rates (15%–20%) . The discrepancies in reported prevalence might be due to small sample sizes, narrow age groups (15–25 years), presence of other disease, inclusion of diagnosed women, and differences in socioeconomic and regional characteristics, lifestyle, and diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder amongst reproductive aged women [ 1 ], with a prevalence of up to 17.8% amongst Australian women [ 2 ]. PCOS is a complex disorder, with reproductive, metabolic and psychological manifestations [ 3 ].…”
Section: Introductionmentioning
confidence: 99%